Breast reconstruction after radical mastectomy for giant phyllodes tumor: a case report - Moises Morales Renteria, Jorge; Ortiz Chang, Emiliano; de la O Escamilla, Manuel Enrique (International Journal of Research in Medical Sciences, 2025)
We present the case of a 40-year-old woman with a giant phyllodes tumor in the left breast, detected after breastfeeding and progressively growing over two years. In August 2023, a biopsy confirmed the diagnosis, and in March 2024, a radical mastectomy was scheduled, as negative surgical margins could not be guaranteed with a conservative approach. The initial intervention included vacuum-assisted closure (VAC) therapy to manage infection risk and prepare the wound for later reconstruction. Thirty days later, breast reconstruction was performed using a latissimus dorsi flap, which was elevated, dissected, and placed over the thoracic defect. The surgery was completed without complications, and the patient had a satisfactory recovery, being discharged three days postoperatively. At the three-month follow-up, the flap showed good integration and favorable evolution. This case highlights the importance of timely breast reconstruction in patients undergoing radical mastectomy for phyllodes tumors and the effectiveness of the latissimus dorsi flap as a reconstructive option in complex scenarios.